2020
DOI: 10.2994/sajh-d-17-00019.1
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates of in Situ Larval Survivorship of the Threatened South American Toad Melanophryniscus montevidensis (Anura, Bufonidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…Our previous studies have shown that adults can select warmer breeding ponds located in sectors of gentle slopes (Goldberg et al 2006). These conditions of breeding sites seem consistent with descriptions for other species of the genus (Pereyra et al 2011;Bardier et al 2020). Warmer water temperatures would permit larval further accelerated developments that would be vitally important at these places where the duration of ponds is short and unpredictable.…”
Section: Phenotypic Plasticitysupporting
confidence: 82%
See 1 more Smart Citation
“…Our previous studies have shown that adults can select warmer breeding ponds located in sectors of gentle slopes (Goldberg et al 2006). These conditions of breeding sites seem consistent with descriptions for other species of the genus (Pereyra et al 2011;Bardier et al 2020). Warmer water temperatures would permit larval further accelerated developments that would be vitally important at these places where the duration of ponds is short and unpredictable.…”
Section: Phenotypic Plasticitysupporting
confidence: 82%
“…Other authors also reported mass mortality of Melanophryniscus sp. tadpoles after the ponds dried out (Cairo et al 2008;Bardier et al 2020). So, in M. rubriventris as it seems in other species of the genus, offspring survival depends more on climatic events that prevent pond drying rather than on developmental plasticity.…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…Our results indicate that the abundance of P. nattereri was asso- Besides survival, density dependence can also affect anuran development (e.g., Bardier et al, 2020;Harper & Semlitsch, 2007;Travis & Trexler, 1986). This might explain why cerrado sensu stricto (vegetation type with the lowest abundance; N = 36) not only had on average larger individuals, but also smaller estimated mortality rates than cerradão (highest abundance; N = 113).…”
Section: Discussionmentioning
confidence: 71%
“…Although we did not detect a significant effect of distance from ephemeral ponds on P. nattereri survival, our study only dealt with juvenile and adult stages, and the possible effects of this variable on the larval stage are still unknown. Besides survival, density dependence can also affect anuran development (e.g., Bardier et al, 2020; Harper & Semlitsch, 2007; Travis & Trexler, 1986). This might explain why cerrado sensu stricto (vegetation type with the lowest abundance; N = 36) not only had on average larger individuals, but also smaller estimated mortality rates than cerradão (highest abundance; N = 113).…”
Section: Discussionmentioning
confidence: 99%